2008
DOI: 10.1103/physrevc.77.054615
|View full text |Cite
|
Sign up to set email alerts
|

Thermal neutron capture cross sections of the palladium isotopes

Abstract: Abstract.We have measured precise thermal neutron capture γ-ray cross sections σ γ for all stable Palladium isotopes with the guided thermal neutron beam from the Budapest Reactor. The data were compared with other data from the literature and have been evaluated into the Evaluated Gamma-ray Activation File (EGAF) [1]. Total radiative neutron capture cross-sections σ 0 can be deduced from the sum of transition cross sections feeding the ground state of each isotope if the decay scheme is complete. The Palladiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 22 publications
(5 reference statements)
4
45
0
Order By: Relevance
“…This expectation is consistent with the observation that differences of experimental MSC spectra from different resonances seem to be very similar to fluctuations among them predicted by simulations using the statistical model. This is also in accord with conclusions made from analysis of TSC [6] and MSC spectra [7] in 96 Mo and indicates that the statistical model can be used for the description of γ decay following radiative neutron capture in even-even nuclei in this mass region.…”
Section: Analysis Of Msc Spectrasupporting
confidence: 76%
See 4 more Smart Citations
“…This expectation is consistent with the observation that differences of experimental MSC spectra from different resonances seem to be very similar to fluctuations among them predicted by simulations using the statistical model. This is also in accord with conclusions made from analysis of TSC [6] and MSC spectra [7] in 96 Mo and indicates that the statistical model can be used for the description of γ decay following radiative neutron capture in even-even nuclei in this mass region.…”
Section: Analysis Of Msc Spectrasupporting
confidence: 76%
“…Analysis in Refs. [6,7] also indicated that the maximum allowed PSFs enhancement is given by a weak resonance postulated near E γ = 1 MeV that reproduces the Oslo experimental data and gives as small as possible PSFs at very low E γ .…”
Section: Psfs That Reproduce Data From 3 He-induced Reactionsmentioning
confidence: 54%
See 3 more Smart Citations